If it's not what You are looking for type in the equation solver your own equation and let us solve it.
g(2g+3)-2=0
We multiply parentheses
2g^2+3g-2=0
a = 2; b = 3; c = -2;
Δ = b2-4ac
Δ = 32-4·2·(-2)
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{25}=5$$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(3)-5}{2*2}=\frac{-8}{4} =-2 $$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(3)+5}{2*2}=\frac{2}{4} =1/2 $
| -4(z-4)+16=-8 | | 9(d+9)+7=97 | | 9(d+9)-7=97 | | 3f2+f=4 | | 2(5+d)-20=-2 | | 1/4+1/2+x=−34 | | 6-3(10+d)=12 | | -19=5s-4 | | M=-11,b=6.2 | | -38=-3w-2 | | -8(z-11)=24 | | 10/7y-3/70=5/2y | | -5(7+b)=-50 | | 3=15-6(4+r) | | 107y−370= 52y | | 180n/n=360 | | -2v-7v=-99 | | -7s-3s=100 | | 10(5+v)=-60 | | 9(d-1)=54 | | 10r-13=-23 | | |x-1|=|x-2| | | 2x^2-13×+15=0 | | 25=-6v+v | | 10x-19=2x+10 | | -3(y+2)=8y-17 | | 15^-10x=11^x-7 | | 2x-1=×+7 | | 3x-15=-6x-3 | | Q-2m-5m-8=3+(-7)+m | | x(.12)+x=94.24 | | 2=4w-2 |